2017
DOI: 10.1186/s12936-017-1879-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of user preferences on ITN use: a review of literature and data

Abstract: BackgroundInsecticide-treated bed nets (ITNs) are the primary tool for vector control, and optimizing ITN use is a key concern of national programmes. Available evidence indicates that bed net users often have preferences for shape, colour, size, and other attributes, but it is unclear whether these preferences are strong enough to have any significant effect on bed net use, and whether countries and donors should invest in more expensive attributes in order to maximize ITN use. The link between bed net attrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 41 publications
(51 reference statements)
9
23
0
1
Order By: Relevance
“…The results of this list randomization experiment suggest very high LLIN usage among household heads in a rural area of a region of The Gambia with high coverage. High usage in a context of high coverage would be good news for public health practitioners worried about disuse and misuse, and is consistent with previous research showing high LLIN use following distribution campaigns [ 25 27 ]. Though list randomization has been shown to be a useful tool for eliciting sensitive behaviours in other contexts, for the specific case of LLIN usage further research is needed.…”
Section: Discussionsupporting
confidence: 89%
“…The results of this list randomization experiment suggest very high LLIN usage among household heads in a rural area of a region of The Gambia with high coverage. High usage in a context of high coverage would be good news for public health practitioners worried about disuse and misuse, and is consistent with previous research showing high LLIN use following distribution campaigns [ 25 27 ]. Though list randomization has been shown to be a useful tool for eliciting sensitive behaviours in other contexts, for the specific case of LLIN usage further research is needed.…”
Section: Discussionsupporting
confidence: 89%
“…High usage in a context of high coverage is good news for public health practitioners worried about disuse and misuse, and is consistent with previous research showing high LLIN use even when not purchased (22)(23)(24). Net distribution campaigns should take into account these results when estimating effectiveness and planning time between interventions.…”
Section: Discussionsupporting
confidence: 85%
“…In fact, an analysis of PMI-country surveys found that the variation of overall durability of ITNs was larger between countries than among net types, although the durability of net types does vary within countries [50,51]. A literature and data review by Koenker and Yukich [52] found that product attributes do not affect use, agreeing with this study which shows NetProtect® was used equally to the other products but was only found to be more durable in Tanzania. The Tanzania NMCP should consider procuring the most appropriate longer-lasting ITN product to be distributed to ensure those nets distributed last for the intended interval between campaigns.…”
Section: Discussionsupporting
confidence: 75%